2020
DOI: 10.1128/mra.00148-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Pseudomonas otitidis Strain MrB4, Isolated from Lake Biwa in Japan

Abstract: We isolated Pseudomonas otitidis strain MrB4 from the near-shore area of Lake Biwa in Japan and generated its complete genome sequence. MrB4 possesses a single circular chromosome of 6,089,454 bp, with ∼97% average nucleotide identity to the P. otitidis type strain MCC10330 (draft genome).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In 2021, the first case of bacteremia was reported [ 4 ]. Previous reports indicate its environmental distribution in Nigeria and Lake Kawaguchi in Japan [ 10 , 11 ], and concerns have been raised regarding its potential to cause infections in immunocompromised patients and more severe presentations [ 2 ]. To the best of our knowledge, this is the first case report of bacteremia caused by P. otitidis in an immunocompromised patient, highlighting the potential risks of severe infections in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the first case of bacteremia was reported [ 4 ]. Previous reports indicate its environmental distribution in Nigeria and Lake Kawaguchi in Japan [ 10 , 11 ], and concerns have been raised regarding its potential to cause infections in immunocompromised patients and more severe presentations [ 2 ]. To the best of our knowledge, this is the first case report of bacteremia caused by P. otitidis in an immunocompromised patient, highlighting the potential risks of severe infections in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup II strains, isolated from infected blood (MRY13-0052) and minced oyster tissue (OT69), clustered together with P. otitidis strain MrB4. Although P. otitidis was initially isolated from a patient with an ear infection, this species is also widespread in nonclinical environments, as was MrB4, isolated from the near-shore area of Lake Biwa in Japan [ 73 ]. In agreement with these results, a recent study showed that a pair-wise comparison of P. alcaligenes OT69 against several type-strain genomes indicated P. otitidis DSM 17224 as its closest relative, rather than the type P. alcaligenes strain NBRC 14159, suggesting that OT69 should be included in a potentially new species [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the rst case of bacteremia was reported [4]. Previous reports indicate its environmental distribution in Nigeria and Lake Kawaguchi in Japan [9,10], and concerns have been raised regarding its potential to cause infections in immunocompromised patients and more severe presentations [2]. To the best of our knowledge, this is the rst case report of severe infection caused by P. otitidis in an immunocompromised patient, highlighting the potential risks of severe infections in such patients.…”
Section: Case Presentationmentioning
confidence: 91%